Analysis of the mediator work of Education Inspectors regarding the regional regulations - Racero Montes, Francisco José; Castillo García, Manuel; Ramos Corpas, Manuel Jesús (Avances en Supervisión Educativa, 2022)
Education inspectors carry out mediation actions in educational centers on a regular basis, this being a highly valued task by all sectors of the educational community. This work makes an approximation to the Alternative Dispute Resolution, later focusing on the regulatory support that each autonomous legislator gives for the exercise of this attribution. A comparative analysis of the regulations of the seventeen Autonomous Communities and the Autonomous Cities of Ceuta and Melilla has been carried out, reaching the conclusion that the regulatory protection is disparate, with a group of Communities that regulate and explain these actions and another group that directly ignore them.
Keywords: education inspectorate; mediation; alternative dispute resolution; educational legislation; autonomous community